Mentalization-Based Parenting Program for Child Maltreatment Prevention: A Pre-Post Study of 12-Week Lighthouse Group Program - Lina Gervinskaitė-Paulaitienė; Gerry Byrne; Rasa Barkauskienė (MDPI AG, 2023)
The aim of this study was to assess the 12-week group version of the mentalization-based Lighthouse Parenting Program for child maltreatment prevention. Parents who might be facing mentalizing difficulties due to challenges in the parent-child relationship were invited to participate in the program. The aim of the program was to promote mentalizing-to encourage parents' curiosity about their children's minds and their willingness to reflect on their own feelings, thoughts, and behaviors. Study participants were 101 parents (82 mothers, 19 fathers). Parenting practices and parental and family adjustment were assessed using the Parent and Family Adjustment Scale and mentalization was measured using Mentalization Scale at pre- and post-intervention assessments. Parents' feedback on the program was gathered after the program. Results revealed that mentalization, parental adjustment, and family functioning improved while coercive parenting practices decreased after the intervention. Study results provide preliminary indications of the benefits of the 12-week Lighthouse Parenting Program for parents referred or self-referred for mental health services due to their own or their child's difficulties.